Lighting up multiprotein complexes: lessons from GPCR oligomerization - Ciruela, Francisco (2010)
Spatiotemporal characterization of protein–protein interactions (PPIs) is essential in determining the molecular mechanisms of intracellular signaling processes. In this review, we discuss how new methodological strategies derived from non-invasive fluorescence- and luminescence-based approaches (FRET, BRET, BiFC and BiLC), when applied to the study of G protein-coupled receptor (GPCR) oligomerization, can be used to detect specific PPIs in live cells. These technologies alone or in concert with complementary methods (SRET, BRET or BiFC, and SNAP-tag or TR-FRET) can be extremely powerful approaches for PPI visualization, even between more than two proteins. Here we provide a comprehensive update on all the biotechnological aspects, including the strengths and weaknesses, of new fluorescence- and luminescence-based methodologies, with a specific focus on their application for studying PPIs.